2001
DOI: 10.1111/j.1530-0277.2001.tb02370.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and Lipid Metabolic Signaling

Abstract: This article represents the proceedings of a symposium at the 2000 ISBRA Meeting in Yokohama, Japan. The chairs were Shivendra D. Shukla and Grace Y. Sun. The presentations were (1) Metabolic turnover of ethanol into cellular lipids and platelet activating factor, by Shivendra D. Shukla; (2) Ethanol action on the phospholipase A 2 signaling pathways in astrocytes, by Grace Y. Sun; (3) Mechanisms of ethanol-induced perturbation of lipoprotein cholesterol transport, by W. Gibson Wood; (4) Transfer of an abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…It is well established that membrane components represent cellular targets of alcohol action. Ethanol-induced alteration of membrane lipids (Shukla et al 2001) might affect the sphingomyelin/ceramide ratio, activating different response elements which may initiate the pathways of cell death (Tepper et al 2000;Mimeault 2002). Recent studies also demonstrated the importance of ceramide generation within caveolae and rafts, which contain diverse signalling response elements (Cremesti et al 2002;Mimeault 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that membrane components represent cellular targets of alcohol action. Ethanol-induced alteration of membrane lipids (Shukla et al 2001) might affect the sphingomyelin/ceramide ratio, activating different response elements which may initiate the pathways of cell death (Tepper et al 2000;Mimeault 2002). Recent studies also demonstrated the importance of ceramide generation within caveolae and rafts, which contain diverse signalling response elements (Cremesti et al 2002;Mimeault 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of N-SMase or A-SMase within the rafts, in response to stress signals, leads to ceramide generation and raft reorganization, facilitating receptor aggregation and the activation of different signalling pathways (Cremesti et al 2002). Ethanol, through its interaction with membrane lipids (Shukla et al 2001), might also induce changes in raft sphingolipids, affecting N/A-SMase and ceramide generation, and promoting the activation of different signalling processes. Alternatively, ethanol induces oxidative stress in astrocytes (Montoliu et al 1995), and several lines of evidence suggest that free radical species and oxidative stress can activate the sphingomyelin-ceramide pathway and apoptotic cell death (Andrieu-Abadie et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, many studies demonstrate that ethanol exposure can enhance or suppress protein kinase C, a signaling pathway that is important in endothelial cell responses, depending on the dose of ethanol [79,80]. Ethanol has also been implicated in membranelipid remodeling, lipid-derived signals, and production of lipid mediators [81]. One study determined that 5% of membrane phospholipids was phosphatidylethanol in ethanol-treated endothelial cells, compared with only 0.5-1% in those cells not treated with ethanol.…”
Section: Acute Ethanol and Wound Angiogenesismentioning
confidence: 98%
“…We have recently revealed the molecular structure of novel endogenous DHA‐derived 14 S ,21‐di‐hydroxy‐docosa‐4 Z ,7 Z ,10 Z ,12 E ,16 Z ,19 Z ‐hexaenoic acid (14 S ,21‐diHDHA) in skin wounds and found that it is a reparative lipid mediator (LM) that promotes wound healing [Lu et al, 2010]. It has been known that AE dysregulates the biosynthesis of LMs [Shukla et al, 2001; Molina, 2008; Sozio and Crabb, 2008]. However, there are no reports regarding the roles of LMs in AE‐impaired wound healing and angiogenesis, no mention of 14 S ,21‐diHDHA.…”
mentioning
confidence: 99%